ACTN3 GENE POLYMORPHISM AND FACTORS ASSOCIATED WITH FUNCTIONAL PERFORMANCE IN ELDERLY WOMEN ASSISTED IN PRIMARY HEALTH CARE - Leandro César Teixeira Machado; Mateus Medeiros Leite; Marina Morato Stival; Yuri Gustavo de Sousa Barbalho; Filipe Dinato de Lima; Luciano Ramos de Lima; Alessandro de Oliveira Silva; Izabel Cristina Rodrigues da Silva; Silvana Schwerz Funghetto (Journal of Physical Education)
ABSTRACT Objective: To analyze potential influences of the R/X genetic polymorphism of the ACTN3 gene, as well as of anthropometric and metabolic characteristics on the functional performance of elderly women assisted in primary health care. Method: One hundred and forty-one elderly women were assessed in terms of anthropometric, metabolic and functional aspects, in addition to clinical, cognitive and demographic characteristics. Allele and genotype frequencies of ACTN3 gene polymorphism were determined. Results: 141 elderly women (68.30 ± 6.18 years) were evaluated. No significant differences (p > 0.05) were observed between the RR and RX/XX genotypes in the elderly women’s functional performance, anthropometric or metabolic characteristics. The TUG test completion time showed positive correlations with age, body mass index, waist circumference, and fat percentage (s = 0.315; p < 0.001; s = 0.238; p = 0.005; s = 0.174; p = 0.039; s = 0.207; p = 0.014), respectively. Negative correlations were found between the TUG test with absolute handgrip strength (s = - 0.314; p < 0.001) and relative handgrip strength (s = - 0.380; p < 0.001). Conclusion: In our study, there were no influences from ACTN3 gene polymorphisms on the functional performance of the elderly women, which is influenced by other factors.